EFFECT OF TESTICULAR TORSION ON SPERMATOZOA IN CONTRALATERAL EPIDIDYMIS - Pramod, Sawkar Vijay; Sugandi, Suwandi; Sihombing, Aaron Tigor; Tan, Marselina (Indonesian Urological Association, 2012)
Objective: To determine the abnormality of spermatozoa in the contralateral epididymis after unilateral testicular torsion. Material & method: Twenty wistar rats were divided into two groups i.e. Group B (sham procedure) Group A (torsio and orchiectomy 24 hours later), and contralateral epididymectomy was performed a month later. Spermatozoa in the contralateral epididymis are extracted and analyzed by an experienced biologist. Data were analyzed using Chi-square or Fischer exact test. Results: Sperm morphology changes in group B is higher than Group A (6,6% vs 0,5%, p = 0,009). Conclusion: Unilateral testicular torsion causes sperm abnormal morphology in the contralateral epididymis. Keywords: Unilateral testicular torsion, contralateral epididimal spermatozoa.